O sistema nacional de atendimento socioeducativo (SINASE) e os desafios das unidades de internação no Distrito Federal - Silva, Edson Mendes da (2015)
This present work concerns the actual landscape of Socio-educational System of the Federal District (Sistema Socioeducativo do Distrito Federal) regarding the socioeducational measures related to the implementation of Socio-educational Service National System (Sistema Nacional de Atendimento Socioeducativo - SINASE) within the confinement procedure. The Statute of Children and Adolescents (Estatuto da Criança e do Adolescente - ECA) and therefore the SINASE has been subject to criticism regarding its services to adolescents in conflict with the law and the incompetence to contain the practice of illegal acts among children under 18 years. Two decades following the creation of ECA, its service is still lies behind the expectations contained in the legislation, the difficulties about taking care of those youngsters have been enabling not just perpetuation of legal infringement, but also its aggravation. The way the socio-educational system works not reach his goal of breaking the offense conduct of adolescents in conflict with the law, but only content to stop temporarily the teenager. The route followed by the Socio- Educational System points to the "dehumanization" increasing the service, since the ideal of rehabilitation has been passed over in the course of care, so that the socioeducational measure, has ceased to be an emancipatory means for be in itself an end. Therefore, we aim to further the debate on socio-educational service on the Federal District, relative to SINASE and according to the contemporaneous global context and its implications.